The Relationship between Social Status and Students Consumptive Behaviour - Layli Triana; Nanang Martono (The Journal of Society and Media, 2021)
Globalization has had some effects the evolution of game forms from traditional to modern. Online games are one of the most common types of modern games. Online games are games that can be accessed by internet-connected and are played on computers, laptops, cellphones, and other devices. Mobile Legends: Bang Bang (MLBB) is the most popular online games in Indonesia. Playing mobile legends online games can have an impact on consumptive behavior among college students. This article explains the relationship between social status and consumptive behavior of Soedirman E-sport Unsoed and explain the relationship between the frequency of playing Mobile Legend Bang-bang (MLBB) with the consumer behavior of Sudirman E-sport students of Jenderal Soedirman University. This study uses a survey method and takes a random sample of 200 members of the Soedirman E-sport Unsoed. The number of samples taken was 67 students. The results showed that first, social status variables were positively related to student consumptive behavior. Both have a correlation value of 0.328 with a significance level of 0.004. The higher the social status, the higher the consumptive behavior of students. Second, the frequency of playing mobile legends online games is positively related to consumptive behavior.